Distribution and sources of organic matter in size-fractionated nearshore sediments off the Barcelona city (NW Mediterranean). (5th April 2017) - Quirós-Collazos, Lucía; Pedrosa-Pàmies, Rut; Sanchez-Vidal, Anna; Guillén, Jorge; Duran, Ruth; Cabello, Patricia
Abstract: Continental shelves are recognized to play a key role in the biogeochemical cycle of carbon, linking terrestrial and marine carbon reservoirs. In this study we investigate the physical and biogeochemical processes that control the source, transport and fate of organic carbon (OC) in the continental shelf off Barcelona city, in the NW Mediterranean Sea. Surface sediment samples were collected from depths of 10–40 m during late summer and autumn 2012. Grain size and biogeochemical parameters such as OC, its stable isotope δ 13 C, total nitrogen (TN) and OC/TN ratios were analysed in size-fractionated sediments. The influence of environmental factors over the study area was determined using hydrological and oceanographic time series, together with video images of the Barcelona coast line and nearshore region. We have found a wide range of OC contents, from 0.13 to 8.68%, depending on water depth and sediment particle size. The highest OC concentration was always found in the clay fraction (<4 μm), followed by the sand fraction (>63 μm) that contained terrestrial plant debris. Wave activity, discharge of the Besòs River and the "Espigó de Ginebra" outfall were the main mechanisms controlling the sorting of sediments by their grain size and thus the distribution of OC in the inner shelf off Barcelona. In addition, we observed that the organic matter in clay particles was progressively degraded seawards, probably because these particles remain suspended in the water column much more time compared to those that are heavier and, therefore, they are exposed for longer time periods to oxygenated conditions. Both OC/TN ratios and δ 13 C values found suggest that the organic matter preserved was predominantly land supplied. Highlights: Organic carbon (OC) on the shelf off Barcelona is dominated by land based sources. Waves and outfall discharge determine grain-size and OC loading of seafloor. Plant debris and OC adsorbed to clays account for most of the OC in sediments. High remineralisation rates are found in this nearshore environment.